Poder y Constitución: la argumentación de la doctrina de las reformas constitucionales inconstitucionales en la jurisprudencia del Tribunal Constitucional peruano y sus problemas - Valdivia Aguilar, Trilce (2024)
This work has the purpose of clarifying and critically evaluating the doctrine of «unconstitutional constitutional amendments» of the Peruvian Constitutional Tribunal. From a mainly constitutional perspective, although complimented with a legal philosophy approach, this work defends that the Constitutional Tribunal basically maintains a substantialist or value-based conception of the Constitution where constitutional amendments are subject not only to institutional limits, but also to material limits. It is also evident that this implicit conception, despite its plausibility, suffers from important imbalances that need to be corrected.